The Influence of Learning Motivation and Self-Efficacy on Accounting Understanding (Case Study at Institute of Information Technology and Business) - Sabaruddin Chaniago (Yayasan Bina Bisnis Nusantara Medan, 2024)
This study seeks to examine the impact of learning motivation and self-efficacy on students' comprehension of accounting at the Institute of Information Technology and Business. Motivation for learning and self-efficacy are two critical psychological elements that are thought to influence academic performance, particularly in accounting disciplines that are sometimes seen as intricate. This research employs a quantitative methodology via a survey technique. Data were gathered from 85 accounting students via a questionnaire structured on a Likert scale. We performed data analysis utilizing multiple linear regression to assess the influence of each independent variable on the dependent variable. The findings indicated that learning motivation and self-efficacy had a favorable and substantial influence on accounting comprehension. Our findings indicate that learning motivation exerted a more significant influence than self-efficacy; nonetheless, both factors concurrently enhanced students' comprehension of accounting concepts. These findings emphasize the necessity of formulating instructional techniques that enhance students' learning motivation and self-efficacy to augment their comprehension of accounting. This study offers pragmatic advice for educators and academic institutions to include these psychological aspects in the learning process